The use of shredded plastic wastes in Alker production and its effect on compressive strength and shrinkage properties - Aya Ahmad (Elsevier, 2022)
Earthen buildings have gained popularity in recent years due to their eco-friendly sustainability approach in both materials and production technique. The materials' availability, ease of construction, and energy efficiency contribute to the utilization of wastes and the reduction of greenhouse gas emissions. Gypsum and shredded plastic wastes are utilized in the production of modified Alker which is an improved earthen building. X-ray Powder Diffraction analysis is performed on the soil to obtain the basic elements in the soil, which show significant Magnesia content. The research studies the mechanical properties in Alker having 6% clay and modified with different percentages of SPW content by dry weight of the soil; 0.5%, 1% and 1.5%. The mechanical properties of matrix modified with 1% SPW show the best results. In addition, linear shrinkage tests are performed on the control and modified sample. The optimum sample modified with 1% SPW show significant reduction in linear shrinkage which is consistent with the crack analysis result performed using Matlab R2018a. It is observed that the optimum sample of 1% SPW has limited crack propagation compared to the other samples. Alker modified with shredded plastic wastes has shown to be a sustainable building material with improved properties.